CONTROLS OF SHEAR ZONE RHEOLOGY AND TECTONIC LOADING ON POSTSEISMIC CREEP - Montési L.G.J. (My University, 2004)
Postseismic deformation is well documented in geodetic data collected in the aftermath of large earthquakes. In the postseismic time interval, GPS is most sensitive to creep in the lower crust or upper mantle activated by earthquake-generated stress perturbations. In these regions, deformation may be localized on an aseismic frictional surface or on a ductile shear zone. These two hypotheses imply specific rheologies and therefore time dependence of postseismic creep. Hence postseismic creep constitutes a potential probe into the rheology of aseismic regions of the lithosphere. I present a simple shear zone model of postseismic creep in which the rheology of the creeping element can be varied. In the absence of tectonic loading during the postseismic time interval, the displacement history of the shear zone obeying a power law rheology with stress exponent n follows an analytical relaxation curve parameterized by 1/n. For a frictional surface, postseismic creep follows the same relaxation law in the limit 1/n → 0. A rough estimate of the apparent stress exponent can be obtained from continuous GPS records. Application to data collected after the 1994 Sanriku earthquake yields 1/n ∼ 0.1, which is consistent with dislocation creep mechanisms. However, the records of two other subduction zone events, the 2001 Peru event and the 1997 Kronotski earthquake, and a continental strike-slip earthquake, the 1999 İzmit earthquake, require negative 1/n. Rather than characterizing the shear zone rheology, these negative exponents indicate that reloading of the shear zone by tectonic forces is important.
Keywords: postseismic; rheology; stress